Factors Associated with Patients' Connection to Referred Social Needs Resources at a Federally Qualified Health Center - Tyler Lian; Kate Kutzer; Diwas Gautam; Howard Eisenson; Jane C. Crowder; Emily Esmaili; Sahil Sandhu; Lawrence Trachtman; Janet Prvu Bettger; Connor Drake (SAGE Publishing, 2021)
Introduction: In an effort to improve health outcomes and promote health equity, healthcare systems have increasingly begun to screen patients for unmet social needs and refer them to relevant social services and community-based organizations. This study aimed to identify factors associated with the successful connection (ie, services started) to social needs resources, as well as factors associated with an attempt to connect as a secondary, intermediate outcome. Methods: This retrospective cohort study included patients who had been screened, referred, and subsequently reached for follow-up navigation from March 2019 to December 2020, as part of a social needs intervention at a federally qualified health center (FQHC). Measures included demographic and social needs covariates collected during screening, as well as resource-related covariates that characterized the referred resources, including service domain (area of need addressed), service site (integration relative to the FQHC), and access modality (means of accessing services). Results: Of the 501 patients in the analytic sample, 32.7% had started services with 1 or more of their referred resources within 4 weeks of the initial referral, and 63.3% had at least attempted to contact 1 referred resource, whether or not they were able to start services. Receiving a referral to resources that patients could access via phone call or drop-in visit, as opposed to resources that required additional appointments or applications prior to accessing services, was associated with increased odds (aOR 1.95, 95% CI 1.05, 3.61) of connection success, after adjusting for age, sex, race, ethnicity, education, number of social needs, and resource-related characteristics. This study did not find statistically significant associations between connection attempt and any variable included in adjusted analyses. Conclusion: These findings suggest that referral pathways may influence the success of patients' connection to social needs resources, highlighting opportunities for more accessible solutions to addressing patients' unmet social needs.